2015
DOI: 10.1097/mco.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient deficiencies in inflammatory bowel disease

Abstract: Micronutrient deficiencies are common and have clinical significance. High suspicion for micronutrient deficiencies is advocated so that treatable causes of morbidity are treated appropriately and late and irreversible sequlae are prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 50 publications
1
164
2
1
Order By: Relevance
“…A lack of iron is present in 30% to 90% of anemic IBD patients [16] and zinc deficiency is associated with a poor disease outcome and a higher risk for disease-related complications [52]. The daily intake of these minerals, as well as of potassium and magnesium, was in accordance with the recommendations of DACH in all our study participants.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 55%
See 2 more Smart Citations
“…A lack of iron is present in 30% to 90% of anemic IBD patients [16] and zinc deficiency is associated with a poor disease outcome and a higher risk for disease-related complications [52]. The daily intake of these minerals, as well as of potassium and magnesium, was in accordance with the recommendations of DACH in all our study participants.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 55%
“…Summarizing the use of vitamins (6%), minerals (4%) and combinations (15%) of the IBD patients in our study the prevalence was 25% and confirmed former results. Since micronutrients deficiencies were described in over 50% of IBD patients [16], it is highly recommended to monitor the vitamin and micronutrient status and apply dietary supplementation to prevent or treat deficiencies.…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…This may vary from only mild alterations in trace elements to severe malnutrition with great weight loss due to the involvement of the gastroin-testinal tract and its effects on food intake and absorption. 4,[22][23][24] Malnutrition is especially common in active UC patients after long-term hospitalization; 11,25 however, few studies have evaluated the nutritional status in patients with UC during remission. 4,12,26,27 Only one trial found a more compromised nutritional status (body weight and BMI) in UC patients during remission than in a control group.…”
Section: Discussionmentioning
confidence: 99%
“…According to available data, malnutrition affects 65-75% of patients with CD and 18-62% of patients with UC [34,35]. In pediatric IBD patients, malnutrition frequently results not only in weight loss but also in growth retardation [36,37].…”
Section: Nutritional Status Of Ibd Patientsmentioning
confidence: 99%